The Use of a Supplementary Online Learning Course, and its Effect on Academic Achievement within an Undergraduate Nursing Programme - Mc Kee, Gabrielle (My University, 2010)
Background: There has been much research into innovations, quality, barriers and satisfaction with online learning. In the rush for development however, there has been little empirical evidence of the effectiveness of online courses in promoting student learning. Study Aim: The aim of this study was to examine the influence of an online learning course on student exam results. Methods: The study design was a cross-sectional survey. The online learning course was supplementary material for a first year biological sciences module in a four year nursing degree programme. Students? access to the course was monitored automatically throughout the academic year. Student exam results and profile were collated from the School database. The data was analysed using SPSS version 16. Results: 195 students participated in the study of which 95% were female and 36% mature students. The sample consisted of students from two strands of the degree: General nursing (84%) and Intellectual Disability (ID) nursing (16%). There was a significant difference in the exam results of General and ID nursing students. There was a significant difference in the usage of the online course depending on mode of entry to the degree programme with mature students making greater use of the online learning course. Spearman's correlation identified a very significant relationship between exam results and usage of the online course (n = 185, r = 0.288, p = 0.0001 (one tailed)). This indicated that usage of the online course accounted for 8% of the variability in exam results. Conclusions: This study would appear to indicate that usage of the online course was related to improved higher exam results as students who used it most had better exam results. These findings go some way in establishing the evidence that is needed to justify the time, effort and cost of the implementing online courses.
PUBLISHED
Keywords: online learning; nurse education; online learning; nurse education